A novel prime numbers-based PV array reconfiguration solution to produce maximum energy under partial shade conditions. (October 2021) - Rezazadeh, Sevda; Moradzadeh, Arash; Hashemzadeh, Seyed Majid; Pourhossein, Kazem; Mohammadi-Ivatloo, Behnam; Hosseini, Seyed Hossein
Abstract: Non-uniform solar irradiance on the photovoltaic arrays decreases the output power due to the partial shading conditions. In this paper, the distribution of shade in the photovoltaic array rows is done by reconfiguring the shaded modules related to the photovoltaic array. The method proposed in this paper is a static approach based on prime numbers. Due to the pattern of prime numbers, it reconfigures the shaded modules in each row. The effectiveness of the proposed procedure is done by testing five different shading patterns in 9 × 9 and one 23 × 23 Total-Cross-Tied PV arrays. The ability and superiority of the proposed method are tested by comparing the results of the suggested method of prime numbers with the results of the Total-Cross-Tied, Sudoku, optimal Sudoku, improved Sudoku, and Dominance square methods. Comparison and evaluation of the results are done by different statistical performance indicators. The evaluations showed that the prime numbers procedure with the values of 9.15%, 7.72%, 8.21%, 8.83%, 8.95%, and 8.77% for cases 1 to 6, respectively, had the highest power factor compared to other methods employed. In addition, the suggested method has the lowest mismatch power losses compared to other procedures by achieving the values of 3.84%, 4.87%, 4.53%, 4.10%, 3.97%, and 4.19% in cases 1–6, respectively. The results of the comparisons strongly emphasize the high ability of the proposed method compared to other methods studied. It should be noted that scalability, high-performance speed, and low cost are important advantages of the prime number method so that this method can be implemented on real-world PV arrays.